2018
DOI: 10.1016/j.jshs.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Are we leveling the playing field? Trends and disparities in sports participation among sexual minority youth in Canada

Abstract: PurposeSports participation and physical fitness are widely beneficial for young people, yet activity levels among young people are declining. Despite growing popular media attention on the participation of sexual minority (e.g., lesbian, gay, and bisexual) youth in sports and various campaigns to improve the often homophobic climate of sports, there is limited evidence that sexual minority youth participate in sports. Our aim was to provide a current portrait of sports participation among 3 groups of sexual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 22 publications
2
24
0
1
Order By: Relevance
“…Greenspan, Griffith, and Watson (2019) found evidence is stronger for males than it is for females and trans people, concluding, there is now "ample data to suggest the prejudicial nature (of sport environments) can serve as a deterrent for athletic participation for gay males, in particular, as this population appears to be targeted harshly" (p. 181-182). Their conclusions are supported by recent population studies by the CDC (Kann et al, 2016(Kann et al, , 2018, and by public health researchers in Canada who have found young gay males play team sports at half the rate (32.8% vs. 67.6%) of peers (Doull, Watson, Smith, Homma, & Saewyc, 2018). The CDC (Kann et al, 2018) reports lesbian (51.7%) and bisexual (38.1%) girls also play team sports at lower rates than their heterosexual peers (61.2%), but the impacts of sexuality-based discrimination is less clear because sexist and homophobic discrimination is intertwined for females in sport (Krane, 1997;Robertson et al, 2019;Storr et al, 2017;Symons et al, 2016).…”
Section: Impact Of Stigma and Discriminatory Language In Sportmentioning
confidence: 68%
“…Greenspan, Griffith, and Watson (2019) found evidence is stronger for males than it is for females and trans people, concluding, there is now "ample data to suggest the prejudicial nature (of sport environments) can serve as a deterrent for athletic participation for gay males, in particular, as this population appears to be targeted harshly" (p. 181-182). Their conclusions are supported by recent population studies by the CDC (Kann et al, 2016(Kann et al, , 2018, and by public health researchers in Canada who have found young gay males play team sports at half the rate (32.8% vs. 67.6%) of peers (Doull, Watson, Smith, Homma, & Saewyc, 2018). The CDC (Kann et al, 2018) reports lesbian (51.7%) and bisexual (38.1%) girls also play team sports at lower rates than their heterosexual peers (61.2%), but the impacts of sexuality-based discrimination is less clear because sexist and homophobic discrimination is intertwined for females in sport (Krane, 1997;Robertson et al, 2019;Storr et al, 2017;Symons et al, 2016).…”
Section: Impact Of Stigma and Discriminatory Language In Sportmentioning
confidence: 68%
“…Research suggests these benefits may only be gained when participation occurs in a supportive environment. 10 Together, these findings indicate a clear need for effective interventions to stop homophobic language in sport. Unfortunately, the reasons why this language remains commonplace, despite positive shifts in public attitudes toward the acceptance of gay and bisexual people in western societies, 11 remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…8 Canadian research has found gay youth play team sports at half the rate (32.8% vs. 67.6%) of heterosexual males. 9 Research indicates gay and bisexual males may avoid sport because they view the use of homophobic language as expressions of homophobic attitudes by teammates and feel unsafe and unwelcome. 1 A review by Greenspan and colleagues concluded, "there is ample data to suggest the prejudicial nature of (sport environments) can serve as a deterrent for athletic participation for gay males."…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, while these shifts in youths' preferences for sport and physical activity have been occurring, participation rates seem to be declining in organized sport among 2 of 15 youth in western countries [7,8]. A report by a Canadian non-profit organization found that although most Canadian youth do in fact participate in sport, the amount of sport and physical activity practiced is not enough to meet daily physical activity requirements [9].…”
Section: Introductionmentioning
confidence: 99%